The financial benefits of the IMF - Bakker, Age F. P.; Schrijvers, Martijn A. (PSL Quarterly Review, 2012)
The IMF provides loans to countries in financial distress at a relatively low interest rate. In this article we calculate how much the seven largest debtors to the IMF have saved on interest payments during the Asian crisis and its aftermath. We explain how the IMF can charge these low interest rates and at what cost for creditor countries. The conditionality attached to the use of IMF resources in the form of policy measures reduces moral hazard behaviour; we argue that this is a better instrument than raising interest rates on IMF loans. JEL Codes: F34, F32, F33, O16